Genome Editing in Animals Methods and Protocols - Hatada, Izuho (Methods in Molecular Biology, 2017)
This volume details protocols that can be used for generation of knockout animals. Chapters guide the reader through basic protocols for three genome editing technologies, target design tools, and specific protocols for each animal. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Genome Editing in Animals: Methods and Protocols aims to ensure successful results in the further study of this vital field